Colloquial French 2 the next step in language learning - Broady, Elspeth (Routledge, 2003)
Do you know French already and want to go a stage further? If you're planning a visit to France, need to brush up your French for work, or are simply doing a course, Colloquial French 2 is the ideal way to refresh your knowledge of the language and to extend your skills. Colloquial French 2 is designed to help those involved in self-study, and structured to give you the opportunity to listen to and read lots of modern, everyday French. It has been developed to work systematically on reinforcing and extending your grasp of French grammar and vocabulary. Key features of Colloquial French 2 include: * a broad range of everyday situations, focusing on France and the wider francophone world * revision: material to help consolidate and build up your basics * a wide range of contemporary documents * spoken and written exercises in each unit * highlighted key structures and phrases, a grammar reference and detailed answer keys * supplementary exercises and French language web-links at www.routledge.com/colloquials/french Accompanying audio material is available to purchase separately on two CDs or in MP3 format, or comes included in the great value Colloquial French 2 pack. Recorded by native speakers, this material includes scripted texts, dialogues and extracts from authentic interviews plus interactive exercises which will help you perfect your pronunciation and listening skills